2021
DOI: 10.1002/advs.202100787
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐Like Fusogenic Liposome‐Mediated Targeting Delivery of miR‐21 Improves Myocardial Remodeling by Reprogramming Macrophages Post Myocardial Ischemia‐Reperfusion Injury

Abstract: Inflammatory modulations focusing on macrophage phenotype are promising candidates to promote better cardiac healing post myocardial ischemia‐reperfusion (MI/R) injury. However, the peak of monocyte/macrophage recruitment is later than the time when enhanced permeability and retention effect disappears, which greatly increases the difficulty of reprogramming macrophages through systemic administration. Meanwhile, the inability of nanomaterials to release their contents to specific intracellular locations throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…In addition to cardiovascular diseases such as ischemic heart disease, hypertension, and arrhythmia, inflammation also plays an important role in heart failure ( Pieske et al, 2019 ; Groenewegen et al, 2020 ; Schiattarella et al, 2020 ). Studies have shown that inflammatory factors can lead to ventricular remodeling, which in turn affects the development of heart failure ( Al-Taweel et al, 2017 ; Tan et al, 2021 ; Yan et al, 2021 ). In addition, there are also animal studies and clinical studies focusing on the positive effects of anti-inflammatory treatments on cardiovascular diseases ( Bäck and Hansson, 2015 ; Huang and Frangogiannis, 2018 ; Ma et al, 2019 ; Gao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to cardiovascular diseases such as ischemic heart disease, hypertension, and arrhythmia, inflammation also plays an important role in heart failure ( Pieske et al, 2019 ; Groenewegen et al, 2020 ; Schiattarella et al, 2020 ). Studies have shown that inflammatory factors can lead to ventricular remodeling, which in turn affects the development of heart failure ( Al-Taweel et al, 2017 ; Tan et al, 2021 ; Yan et al, 2021 ). In addition, there are also animal studies and clinical studies focusing on the positive effects of anti-inflammatory treatments on cardiovascular diseases ( Bäck and Hansson, 2015 ; Huang and Frangogiannis, 2018 ; Ma et al, 2019 ; Gao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo macrophage targeting of Cy5-siRNA-containing NCs was further explored via flow cytometry. In the early stage of reperfusion (several hours to several days after IR), pro-inflammatory M1-type macrophages occupy a greatly larger proportion than anti-inflammatory M2-type macrophages in the injured myocardium [ [58] , [59] , [60] , [61] ]. Thus, the proportion of M1-or M2-type macrophages in the injured heart and the internalization of Cy5-siRNA-containing NCs in them were monitored.…”
Section: Resultsmentioning
confidence: 99%
“… Shi et al (2018) identified that miR-21, an exosome derived from MSCs, down-regulated the expression of PTEN by activating the PI3K/AKT signaling pathway, thereby protecting cardiomyocytes from death induced by ischemia and oxidative stress. In addition, the latest study found that miRNA-21 can also improve myocardial remodeling after myocardial ischemia-reperfusion injury by reprogramming macrophages ( Tan et al, 2021 ). Reprogrammed macrophages coordinate the remodeling of the myocardial microenvironment in the anti-inflammatory treatment of ischemia reperfusion (IR) injury ( Tan et al, 2021 ).…”
Section: Exosomes and Mesenchymal Stem Cellsmentioning
confidence: 99%
“…In addition, the latest study found that miRNA-21 can also improve myocardial remodeling after myocardial ischemia-reperfusion injury by reprogramming macrophages ( Tan et al, 2021 ). Reprogrammed macrophages coordinate the remodeling of the myocardial microenvironment in the anti-inflammatory treatment of ischemia reperfusion (IR) injury ( Tan et al, 2021 ). MiR-30c-5p can down-regulate BCL2-like 11 (BCL2L11) to improve myocardial injury, histopathological changes and apoptosis in rat I/R model ( Meng et al, 2021 ).…”
Section: Exosomes and Mesenchymal Stem Cellsmentioning
confidence: 99%